In vivo tumor surveillance by NK cells requires TYK2 but not TYK2 kinase activity - Michaela Prchal-Murphy; Agnieszka Witalisz-Siepracka; Karoline T Bednarik; Eva Maria Putz; Dagmar Gotthardt; Katrin Meissl; Veronika Sexl; Mathias Müller; Birgit Strobl (OncoImmunology, 2015)
Tyrosine kinase 2 (TYK2) is a Janus kinase (JAK) that is crucially involved in inflammation, carcinogenesis and defense against infection. The cytotoxic activity of natural killer (NK) cells in TYK2-deficient (Tyk2−/−) mice is severely reduced, although the underlying mechanisms are largely unknown. Using Tyk2−/− mice and mice expressing a kinase-inactive version of TYK2 (Tyk2K923E), we show that NK cell function is partly independent of the enzymatic activity of TYK2. Tyk2−/− and Tyk2K923E NK cells develop normally in the bone marrow, but the maturation of splenic Tyk2−/− NK cells (and to a lesser extent of Tyk2K923E NK cells) is impaired. In contrast, the production of interferon γ (IFNγ) in response to interleukin 12 (IL-12) or to stimulation through NK cell-activating receptors strictly depends on the presence of enzymatically active TYK2. The cytotoxic activity of Tyk2K923E NK cells against a range of target cells in vitro is higher than that of Tyk2−/− NK cells. Consistently, Tyk2K923E mice control the growth of NK cell-targeted tumors significantly better than TYK2-deficient mice, showing the physiological relevance of the finding. Inhibitors of TYK2's kinase activity are being developed for the treatment of inflammatory diseases and cancers, but their effects on tumor immune surveillance have not been investigated. Our finding that TYK2 has kinase-independent functions in vivo suggests that such inhibitors will leave NK cell mediated tumor surveillance largely intact and that they will be suitable for use in cancer therapy.